Legacies of Space and Intangible Heritage Archaeology, Ethnohistory, and the Politics of Cultural Continuity in the Americas - Armstrong-Fumero, Fernando (University Press of Colorado, 2017)
This volume looks at how different physical environments contribute to the reproduction of cultural forms even in the wake of colonization, migration, and other processes of displacement and change. This raises the question of whether cultural practices are altered by changes in physical environment or if a group's narratives and practices shape their location. Using case studies from North and South America, the contributors reveal a pattern of abandonment and reestablishment of settlements and how collective memory drives people back to culturally meaningful sites. Through the lenses of archaeology and ethnohistory and by examining the politics of cultural continuity, the authors argue that there is a complex relationship between a people's heritage and the landscape that affects the making of "place."